U(VI) binding onto electrospun polymers functionalized with phosphonate surfactants. Issue 5 (October 2022) - Shaikh, Nabil; Qian, Jiajie; Kim, Sewoon; Phan, Hoa; Lezama-Pacheco, Juan S.; Ali, Abdul-Mehdi S.; Cwiertny, David M.; Forbes, Tori Z.; Haes, Amanda J.; Cerrato, José M.
Abstract: We previously observed that phosphonate functionalized electrospun nanofibers can uptake U(VI), making them promising materials for sensing and water treatment applications. Here, we investigate the optimal fabrication of these materials and their mechanism of U(VI) binding under the influence of environmentally relevant ions (e.g., Ca 2+ and CO3 2- ). We found that U(VI) uptake was greatest on polyacrylonitrile (PAN) functionalized with longer-chain phosphonate surfactants (e.g., hexa- and octadecyl phosphonate; HDPA and ODPA, respectively), which were better retained in the nanofiber after surface segregation. Subsequent uptake experiments to better understand specific solid-liquid interfacial interactions were carried out using 5 mg of HDPA-functionalized PAN mats with 10 μM U at pH 6.8 in four systems with different combinations of solutions containing 5 mM calcium (Ca 2+ ) and 5 mM bicarbonate (HCO3 - ). U uptake was similar in control solutions containing no Ca 2+ and HCO3 - (resulting in 19 ± 3% U uptake), and in those containing only 5 mM Ca 2+ (resulting in 20 ± 3% U uptake). A decrease in U uptake (10 ± 4% U uptake) was observed in experiments with HCO3 -, indicating that UO2 -CO3 complexes may increase uranium solubility. Results from shell-by-shell EXAFS fitting, aqueous extractions, and surface-enhanced Raman scattering (SERS) indicate that U is bound to phosphonate as a monodentate inner sphere surface complex to one of the hydroxyls in the phosphonate functional groups. New knowledge derived from this study on material fabrication and solid-liquid interfacial interactions will help to advance technologies for use in the in-situ detection and treatment of U in water. Graphical Abstract: ga1 Highlights: Electrospun phosphonate functionalized nanofibers show uptake of uranium (U). Presence of calcium and carbonate affect the uptake of U due to aqueous U speciation. The U-Phosphonate binding is consistent in all the system despite the differences in uptake. U is bound as a monodentate inner sphere surface complex to one of the hydroxyls in the phosphonate functional groups.